Multidimensional predictors of cognitive impairment among community-dwelling older adults in Klang Valley, Malaysia - Lim, Shiang Cheng (2016)
Cognitive decline and cognitive impairment among older adults is a rising public health concern. It is a costly condition that affects individuals, families and countries which often associated with increased risk of dementia, disability and mortality. Numerous risk factors associated with cognitive impairment have been identified but early identification of cognitive impairment is rare and little is known about the risk profile among Malaysians. There is lack of multidimensional risk model, which synthesizes information from known risk factors of cognitive impairment, particularly the modifiable lifestyle-related risk factors. This study was conducted to determine the risk factors and predictors of cognitive impairment from multidimensional approach, based on a representative sample of the community-dwelling older adult Malaysian population. This study was conducted through a cross-sectional household survey in the Klang Valley using multi-stage sampling. A total of 698 respondents aged 60 years old and above, living in community participated in the study. Multivariate logistic regression analysis was performed to determine the predictors of cognitive impairment. Age, being female, Malay or Indian, education, aerobic activity and physical function were the six predictors identified for cognitive impairment after controlling for other factors including socio-demographic, cardiovascular risk, lifestyle-related risks and psychosocial factors. While advancing age, being female, Malay or Indian were found as the risk factors for cognitive impairment, increasing years of education, aerobic activity and better physical function were associated with the reduced risk of cognitive impairment at p<0.05 level of significance. The predictors for cognitive impairment identified in the study provided a hierarchy of priorities for the development of policies, strategies, programmes and interventions. In view of that, it is crucial to identify individuals who are at higher risk of cognitive impairment and targeted them to encourage lifestyle changes by using life course approach to preserve cognitive function, prevent or delay the onset of cognitive impairment.